Graphical user interface a and device driver for USB controller - 229471 Tan, Kok Boon; Zuraimi Yahya, supervisor; Fakulti Kejuruteraan Elektrik (2005)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2005